Cargo Hold Failure in Meeting the Hospital Clean Standard after Discharging Dirty Cargo and before Loading Grain Cargo on Board MV Bel Air - Dirgantoro, Andika Rivaldi; Purnama, Chanra; Lumban Batu, Purnama NF (Jurnal Cakrawala Bahari, 2025)
This study was initiated due to the MV Bel Air’s failure to achieve the hospital clean standard of cargo hold cleanliness when shifting from loading dirty cargo (coal) to grain cargo (sunflower meal and barley). Two main problems were identified, including the presence of coal stain on the bulkhead, side shell, and topside of cargo hold number 7, and coal residue in the bilges of cargo hold number 1. These issues led to loading delays and demurrage claims. The objective of this study was to investigate the root causes of the cleaning failure and to develop a cleaning strategy that met the required standard. This study utilized a qualitative approach, using data collection techniques such as direct observation and documentation. The data were analyzed by using root cause analysis to identify the contributing factors behind the cargo hold’s failure to meet the hospital clean standard. The findings revealed that the failure was influenced by two key factors. First, the inconsistency between the actual cleaning practices and the standard operation procedures, and the limited availability of cleaning agent along with inadequate equipment. Recommended corrective actions to address these problems included providing training on cleaning procedures, conducting toolbox meeting before cleaning activities, recruiting experienced crew members for cleaning operation, optimizing procurement and inventory management of cleaning equipment, and implementing regular preventive maintenance for cleaning equipment.